Pengaruh Gaya Hidup, Brand Image, Harga, dan Promosi terhadap Keputusan Pembelian pada Dealer Motor Centro Bike Kawasaki Kediri - Erika Sita Hapsari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This research aims to determine the influence of lifestyle variables (X1), brand image (X2), price (X3) and promotion on purchasing decisions (Y) at the Centro Bike Kawasaki Kediri Motorcycle Dealer. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the accidental sampling method, the number of samples in the research was 87 respondents at the Kawasaki Kediri Dealer. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the research obtained the multiple linear regression equation Y= 3.041 + 0.203X1 + 0.220X2 + 0.238X3 + 0.204X4 and the results of the t test for lifestyle variables had a partially significant effect on purchasing decisions with a sig result of 0.022 < 0.05. Brand image has a partially significant effect on purchasing decisions, with the resulting sig value. 0.016 > 0.05. Price has a partially significant effect on purchasing decisions, with the resulting sig value. 0.013 > 0.05. Promotion has a partially significant effect on purchasing decisions, with a sig value. 0.027 > 0.05. The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that lifestyle. Brand image, price and promotion simultaneously and significantly influence purchasing decisions at the Kediri Kawasaki Dealer.